ANALISIS KINERJA KEUANGAN DALAM PENGELOLAAN ANGGARAN DAERAH DI PROVINSI JAWA TIMUR - Zaki Bahrun Ni'am; Chavid Moyo Jaladri; Ulfa, Vida Maria (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
The economic potential of East Java Province is supported by many sectors that are sources of regional income. The problem that forms the basis of this research is that the recapitulation data related to the largest corruption crime in the 2022 period ranks second after the central government. The research-related objective is to analyze the financial performance of the Regional Revenue and Expenditure Budget in East Java Province in 2021-2022. Descriptive quantitative is the type of research used with the 2021-2022 APBD financial report being the source of assessment data. The research sample is the entire population covering 38 regencies/ cities in East Java Province. Research data analysis techniques include; Expenditure variance analysis, expenditure growth analysis, independence ratio, dependency ratio, degree of decentralization, expenditure variance analysis, and expenditure efficiency ratio. The results of the study explained that East Java Province in 2021-2022 based on revenue variance analysis is in the favorable variance category with a percentage of 106.91%, revenue growth analysis is classified as downward growth with a percentage value of -3.21%. The independence ratio shows a participatory relationship pattern with a percentage of 51.24%, the dependency ratio is medium with a percentage of 61.51%.